2018
DOI: 10.1021/acs.energyfuels.8b01350
|View full text |Cite
|
Sign up to set email alerts
|

Porosity of Drill-Cuttings Using Multinuclear 19F and 1H NMR Measurements

Abstract: Petrophysical measurements of drill cuttings are vital for determining reservoir quality in organic mudstone plays, where the highly deviated (horizontal/lateral) production wells are rarely logged. We demonstrate a methodology to measure the porosity of irregularly shaped drill-cutting samples using multinuclear 1H–19F NMR measurements at medium frequencies (12 MHz). The methodology is successfully demonstrated on both core and irregularly shaped simulated cuttings from conventional and unconventional shale p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Some recent work has been performed in source rock cuttings. Multiple studies combined 1 H and 19 F NMR measurements of cuttings saturated with oil or water and surrounded by fluorinated fluid to determine the porosity of the cuttings. , Another examined the kerogen content using diffuse reflectance infrared Fourier transform spectroscopy; however, this method only provides data on the organic matter. In this study, we present a 1 H NMR-based method to measure rock porosity and densities of the whole rock using drill cuttings.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent work has been performed in source rock cuttings. Multiple studies combined 1 H and 19 F NMR measurements of cuttings saturated with oil or water and surrounded by fluorinated fluid to determine the porosity of the cuttings. , Another examined the kerogen content using diffuse reflectance infrared Fourier transform spectroscopy; however, this method only provides data on the organic matter. In this study, we present a 1 H NMR-based method to measure rock porosity and densities of the whole rock using drill cuttings.…”
Section: Introductionmentioning
confidence: 99%
“…They also suggested a method of estimating the total organic carbon (TOC) content of shales which is a useful parameter for the evaluation of shale reservoirs. [30] presented NMR porosity of irregular shaped drill cuttings. They addressed the challenges associated with estimating porosity from drill cuttings by including a higher frequency multinuclear NMR method.…”
Section: Porositymentioning
confidence: 99%
“…In addition, Ortega and Aguilera [8] defined the minimum cutting size of tight sandstone that can be used for porosity measurement to be >1 mm in diameter. For shale, Fellah et al [9] found that shale cuttings with 1-5 mm in diameter provide accurate porosity. For coal, Chang et al [10] found that the porosity and PSD of coal can be found using coal cuttings with diameter > 1 mm.…”
Section: Introductionmentioning
confidence: 99%